PRMT5-mediated histone arginine methylation antagonizes transcriptional repression by polycomb complex PRC2. Issue 6 (6th February 2020) - Liu, Fan; Xu, Ye; Lu, Xiaoqing; Hamard, Pierre-Jacques; Karl, Daniel L; Man, Na; Mookhtiar, Adnan K; Martinez, Concepcion; Lossos, Izidore S; Sun, Jun; Nimer, Stephen D
Abstract: Protein arginine methyltransferase 5 (PRMT5) catalyzes the symmetric di-methylation of arginine residues in histones H3 and H4, marks that are generally associated with transcriptional repression. However, we found that PRMT5 inhibition or depletion led to more genes being downregulated than upregulated, indicating that PRMT5 can also act as a transcriptional activator. Indeed, the global level of histone H3K27me3 increases in PRMT5 deficient cells. Although PRMT5 does not directly affect PRC2 enzymatic activity, methylation of histone H3 by PRMT5 abrogates its subsequent methylation by PRC2. Treating AML cells with an EZH2 inhibitor partially restored the expression of approximately 50% of the genes that are initially downregulated by PRMT5 inhibition, suggesting that the increased H3K27me3 could directly or indirectly contribute to the transcription repression of these genes. Indeed, ChIP-sequencing analysis confirmed an increase in the H3K27me3 level at the promoter region of a quarter of these genes in PRMT5-inhibited cells. Interestingly, the anti-proliferative effect of PRMT5 inhibition was also partially rescued by treatment with an EZH2 inhibitor in several leukemia cell lines. Thus, PRMT5-mediated crosstalk between histone marks contributes to its functional effects.